Implementation of early detection activities for pregnant women with gestational hypertension: Implementasi kegiatan deteksi dini ibu hamil dengan hipertensi kehamilan - Rena Oki Alestari; Neneng Safitri; Lidia Widia; Evy Kasanova (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2026)
One of the pregnancy complications that remains a major cause of maternal mortality (MMR) and infant mortality (IMR) in Indonesia is gestational hypertension. This condition has the potential to cause serious complications for both the mother and the fetus, necessitating early detection, appropriate management, and prompt referral when needed. This community service program aims to provide health education, followed by examinations of pregnant women and early detection of women with gestational hypertension.   Comprehensive Midwifery Care for Mrs. M, 29 Years Old, 33 Weeks Pregnant with Hypertension in Pregnancy at Cempaka Mulia Health Center, East Kotawaringin Regency. In patient Mrs. M, 29 years old with Hypertension in Pregnancy.  Able to provide comprehensive midwifery care since Mrs. M aged 29 years with hypertension with a midwifery management approach. The design used in writing this report is a case study design. Comprehensive Midwifery Care was carried out at the Cempaka Mulia Health Center, from February to April 2025. Pregnancy care for Mrs. M was in accordance with midwifery standards. Mrs. M's delivery care was normal. Mrs. M's care was normal. Mrs. M's postpartum care was provided according to midwifery standards. Family planning care was obtained by the mother who decided to use a 3-month injection. Comprehensive midwifery care for Mrs. M aged 29 years G2P1A0 went physiologically, there were no complications in the mother or baby. This is because the mother and baby have visited the nearest health facility if there are complaints.